Raphaneae: report on the 2005 and 2006 survey - Gschwind, Markus (Zeitschrift für Orient-Archäologie, 2009)
The exact location and extent of the settlement area of Raphaneae (prov. Hama, Syria) has now been determined through surveys. An integrated discussion of surface finds and historical sources provides a better understanding of the development of the legionary fortress and the Roman to Medieval city.